Environmental discourses and the question of creative environment in a city - Kačerauskas, Tomas (Journal of Environmental Engineering and Landscape Management, 2016)
The paper deals with the different environmental discourses and the question whether the city is a creative environment. The theses have been developed as follows: 1) there are different environmental discourses including technological, sociological, ecological, religious, philosophical (ethical), urban, and discourse of creativity; 2) a novelty of a discourse follows from the interdisciplinary character, i.e. From a combination of the discourses; 3) a city both attracts and turns away the creative workers: here there are many occasions of creative activities and spreading of creation, however at the same time there is an anti-ecological environment that also uniforms creation; 4) although cosmopolitanism and globalism are intimately connected, they could be evaluated as two contrary principles: the first one is to be connected with the principle of difference, the latter – with the principle of unification; 5) although there are many debates concerning such social formation as the creative class, it is the main element and engine of a creative society.